Calibration and Laboratory Testing of Computer Measuring System 8AE-PD Dedicated for Analysis of Acoustic Emission Signals Generated by Partial Discharges Within Oil Power Transformers - WITOS, Franciszek; SZERSZEŃ, Grzegorz; OPILSKI, Zbigniew; SETKIEWICZ, Maciej; OLSZEWSKA, Aneta; DUDA, Dominik; MAŹNIEWSKI, Krzysztof; SZADKOWSKI, Marek (Archives of Acoustics, 2017)
In the paper, there are presented a general description of the constructed measuring system 8AE-PD, the results of calibration of this system by the Hsu-Nielsen method as well as the testing of the measuring system during recording signals generated by Hsu-Nielsen sources in a steel plate and a modeled partial discharge (PD) source. There is also presented the methodology of investigations by the calibrated acoustic emission method. The results of analyses of PD signals coming from the modeled sources are given. In particular, there are described the properties of acoustic emission (AE) signals generated by the PDs as well as the dependencies of the peak-to-peak voltage U_mm, the RMS voltage U_rms and the descriptors of acronyms ADP and ADC on the apparent charge Q introduced by the modeled PD source. There are determined the limit values of the apparent charge Q introduced by the modeled PD source for which the recorded signal is identified as originating from the PDS.